Study Of Medicine Plants Ethnobotany In Banceuy Indigenous People Subang Regency, West Java - Jessica Pati Weking, Cornelia; Hafsah, Hafsah; Rahma Lestari, Tami (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
The Kampung adat Banceuy society is one of the indigenous communities of the archipelago that still practice local wisdom insight, such as plants, for medicinal purposes. This study aims to inventory the diversity of medicinal plants used by the people of Kampung adat Banceuy. The research method was done by direct observation and depth interviews with key informants and respondents. The results show that society has used 48 species (28 families) of medicinal plants for generations. The sources of plants are obtained from around settlements that grow wildly or from their garden. The leaf is the most used plant organ. Herbs are the most common plant habitus used. Medicinal plants were used directly or by processing traditionally first. Medicinal plants are planted independently to maintain availability and indirectly for conservation. This society's inventory of medicinal plants expects to be beneficial information for further conservation and development efforts. This study also presented data on plants used by the indigenous people of Banceuy for various needs.